Continuity of Public Insurance Coverage: A Systematic Review of the Literature. (April 2014) - Guevara, James P.; Moon, Jeanhee; Hines, Elizabeth M.; Fremont, Ettya; Wong, Angie; Forrest, Christopher B.; Silber, Jeffrey H.; Pati, Susmita
Publicly financed insurance programs are tasked with maintaining coverage for eligible children, but published measures to assess coverage have not been evaluated. Therefore, we sought to identify and categorize measures of health insurance continuity for children and adolescents. We conducted a systematic review of Medline and HealthStar databases, review of reference lists of eligible articles, and contact with experts. We categorized measures into 8 domains based on a conceptual framework. We identified 147 measures from 84 eligible articles. Most measures evaluated the following domains: always insured (41%), repeatedly uninsured (36%), and transition out of coverage (29%), while fewer assessed single gap in coverage, always uninsured, transition into coverage, change in coverage, and eligibility. Only 18% of measures assessed associations between continuity of coverage and child and adolescent health outcomes. These results suggest that a number of measures of continuity of coverage exist, but few measures have assessed impact on outcomes.